How ESG Disclosure and Political Connections Effect Firm Value? Evidence on Indonesia Non-Financial Companies - Clara Octavia Sitorus; Wahdan Arum Inawati (Politeknik Ganesha Medan, 2026)
This study examines the effect of environmental, social, and governance (ESG) disclosure, along with political connection, on firm value. The sample consists of non-financial companies listed on the Indonesia Stock Exchange during the period 2019 to 2023. The research sample was determined using purposive sampling, based on specific criteria, resulting in 145 observations from 29 companies. Data analysis was conducted using panel regression techniques for hypothesis testing, processed with EViews 12 software. The findings reveal that ESG disclosure and political connection simultaneously have a significant effect on firm value. However, the partial analysis indicates that only environmental disclosure has a significant negative impact on firm value. These results implies that companies should exercise caution when disclosing environmental information, as it can trigger a negative response from investors who perceive it as a cost burden. Meanwhile, social disclosure, governance disclosure, and political connection partialy show no significant effect on firm value. Furthermore, it is recommended to examine other independent variables, such as financial aspects that have the potential to influence firm value. Practical suggestion of this research is companies should adpot more operational and strategic approach in managing environmental costs that need to be integrated into long-term business strategies and linked directly to efficiency improvement.